Correlation between Reflux and multichannel intraluminal impedance pH monitoring in untreated volunteers. (27th May 2014) - Jetté, Marie E.; Gaumnitz, Eric A.; Birchall, Martin A.; Welham, Nathan V.; Thibeault, Susan L.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Although probable causative agents have been identified (e.g., refluxate components, tobacco smoke), the definitive mechanism for inflammation‐related laryngeal mucosal damage remains elusive. Multichannel intraluminal impedance combined with pH monitoring (MII/pH) has emerged as a sensitive tool for diagnosis and characterization of gastroesophageal reflux disease with laryngopharyngeal manifestations. To determine the relationship between laryngeal signs and MII/pH, we examined correlations between Reflux Finding Score (RFS) ratings of videostroboscopic laryngeal examinations and findings from MII/pH. Study Design Correlational study. Methods Healthy, untreated volunteers (n = 142) underwent reflux diagnosis using data acquired from MII/pH testing. Eight trained clinicians performed RFS ratings of corresponding laryngeal examinations. Averaged RFS ratings were compared to MII/pH data using Pearson correlation coefficients. The relationship between RFS and MII/pH findings and demographic/clinical information (age, sex, smoking status, reflux) was assessed using general linear modeling. Rater reliability was evaluated. Results Posterior commissure hypertrophy was negatively correlated with minutes of nonacid refluxate (R = −0.21, P = .0115). General linear modeling revealed that 28% to 40% of the variance in ratings of ventricular obliteration, erythema/hyperemia, vocal fold edema, diffuse laryngeal edema, posterior commissure hypertrophy, and granulation/granuloma could be explained by main and interaction effects of age, sex, smoking status, and reflux. Intra‐ and inter‐rater reliability for RFS were poor–fair. Conclusions These results support the theory that the RFS is not specific for reflux in healthy, untreated volunteers, suggesting there may be alternate explanations for inflammatory clinical signs commonly ascribed to reflux in this population. Level of Evidence 1b Laryngoscope 124:2345–2351, 2014